Determination of Attitudes on Gender: a Study on Higher Education Students - DASLI, Yılmaz; SARICOBAN, Sinem (European Scientific Journal, ESJ, 2016)
In this study, it’s aimed to specify the perspectives, attitudes and the awareness levels of university students on gender. 7,200 students studying at Cumhuriyet University and staying at the Credit and Dormitories Institution constitute the population of the study. Samples selected by random sample method are determined to be 370 individuals. 370 individuals, 185 women and 185 men, have participated in the study, and their average age was 21.47. The monthly income of 62.1% of these students was less than 500 TL, 68.4% of them had a nuclear family type and 43.5% of them has resided in the city center. 68.9% of students have stated that men and women aren’t equal while 37.8% have stated that this inequality arises from the structure of society, 22.4% have stated that the biggest challenge of women is violence and 73.8% have stated that women and men have equal amount of task share for the sexual equality. The results obtained by this study show that when all aspects related to gender roles concerning working life (Table 6), social life (Table 7) and family life (Table 8) of the students are examined, it is observed that male students have a more traditional viewpoint compared to female students and female students have a traditional viewpoint in propositions concerning married life (Table 8).